12.5k views
0 votes
6x-3y= -6 solve for y

User Thermech
by
5.4k points

2 Answers

2 votes

Answer:

First you would subtract 6x from both sides, (you want Y to be alone)

now you have-3y= -6x -6

Then you divide -3 by every number on the right side.

now you have y= 1/2x+1/2

now thats your answer

Explanation:

User ROODAY
by
4.8k points
7 votes

Answer:

The value of the equation for y is
y=2+2x.

Explanation:

Consider the provided equation.


6x-3y= -6

We need to solve the equation for y.

Subtract 6x from both the sides.


6x-6x-3y= -6-6x


-3y= -6-6x

Divide both the sides by -3.


(-3y)/(-3)=(-6-6x)/(-3)


y=(-6)/(-3)(-6x)/(-3)


y=2+2x

Thus, the value of the equation for y is
y=2+2x.

User Claudio Holanda
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.